2023
DOI: 10.1002/advs.202205960
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically Designed Triboelectric Wristbands with Adaptive Accelerated Learning for Human–Machine Interfaces

Abstract: Recent advances in flexible wearable devices have boosted the remarkable development of devices for human-machine interfaces, which are of great value to emerging cybernetics, robotics, and Metaverse systems. However, the effectiveness of existing approaches is limited by the quality of sensor data and classification models with high computational costs. Here, a novel gesture recognition system with triboelectric smart wristbands and an adaptive accelerated learning (AAL) model is proposed. The sensor array is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…A reference electrode was attached at the elbow of the same arm. As the EMG signals reflect the muscle contractions in the forearm, which are triggered by hand squeezing, 50 the participant was asked to maintain different levels of designated grip force (MVC of 25, 50, 75, and 100%). We obtained the EMG signals corresponding to each MVC after filtering them through a biobandpass filter (1−500 Hz).…”
Section: Acnt Sheets Asmentioning
confidence: 99%
“…A reference electrode was attached at the elbow of the same arm. As the EMG signals reflect the muscle contractions in the forearm, which are triggered by hand squeezing, 50 the participant was asked to maintain different levels of designated grip force (MVC of 25, 50, 75, and 100%). We obtained the EMG signals corresponding to each MVC after filtering them through a biobandpass filter (1−500 Hz).…”
Section: Acnt Sheets Asmentioning
confidence: 99%
“…This nonresonant harvester has a broad range of corresponding frequencies, while the omnidirectional structure is also well suited for multi-degree-of-freedom movements. Fang [179] proposed a triboelectric smart wristband based on adaptive accelerated learning that can effectively recognize hand motions, showing high sensitivity and high-quality sensing capabilities.…”
Section: Energy Harvestermentioning
confidence: 99%
“…Mechanical energy from the environment such as wind, vibration, water, and human activities , is a potential sustainable energy. It has been demonstrated that triboelectric nanogenerators (TENGs) exhibited significant advantages in harvesting small random mechanical energy with low frequency and can convert the mechanical energy distributed around into electrical energy. However, the traditional electrode materials used in TENGs are usually metal electrodes, such as copper and silver . Although they have good conductivity, there are still challenges, such as limited flexibility, ductility, and compressibility, leading to electrodes being easily broken when large deformation occurs and fail the entire electronics.…”
Section: Introductionmentioning
confidence: 99%